2013
DOI: 10.3762/bjoc.9.25
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of phenylene-ethynylene rods and their use as rigid spacers in divalent inhibitors

Abstract: SummaryThe synthesis of phenylene-ethynylene rods and their use as rigid spacers is described. Alternation of a Sonogashira reaction and silyl group cleavage was used to obtain rigid spacers with even and odd numbers of phenylene units. Preliminary applications of these rods in divalent systems are shown. Inhibition studies with Pseudomonas Aeruginosa lectin LecA showed that the rigid spacer proved greatly beneficial for the inhibitory potency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…[16] Another approach to enhancei nhibitor interaction to LecA is through multivalent binding. Because LecA is at etrameric lectin andt he two closest binding sites are separated by about 26 , [17] various artificial scaffolds including dendrimers, [11,[18][19][20][21][22][23][24] clusters, [12][13][14][25][26][27][28][29][30][31][32] and linear rigid spacers [33][34][35][36] have been exploited to present galactoside ligands to theb inding sites to enhancei nhibition activity. [37] In other cases, the artificial scaffoldsa re furtherf unctionalized to generate extra interactions with LecA for stronger binding.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Another approach to enhancei nhibitor interaction to LecA is through multivalent binding. Because LecA is at etrameric lectin andt he two closest binding sites are separated by about 26 , [17] various artificial scaffolds including dendrimers, [11,[18][19][20][21][22][23][24] clusters, [12][13][14][25][26][27][28][29][30][31][32] and linear rigid spacers [33][34][35][36] have been exploited to present galactoside ligands to theb inding sites to enhancei nhibition activity. [37] In other cases, the artificial scaffoldsa re furtherf unctionalized to generate extra interactions with LecA for stronger binding.…”
Section: Introductionmentioning
confidence: 99%
“…The linker molecule was synthesized by a combination of the Sonogashira coupling and the deprotection of the trimethylsilyl (TMS) group, which is a typical route to synthesize oligo(phenylene ethynylenes) ( 24 , 25 ). The triphenyl methanol unit was introduced to the periphery by Sonogashira coupling.…”
Section: Resultsmentioning
confidence: 99%
“…Ordanini et al, Pertici et al and Barattucci et al have reported on glycodendrimers containing a rod‐like aromatic core of variable length, which allows to span the large distances that separate lectins' binding sites. A previous study by our group described the synthesis of a series of pseudo‐glycosylated dendrimers (Table ) assembled by linking a rod core and two trivalent dendrons.…”
Section: Introductionmentioning
confidence: 99%